Impact of Port Digitalization on Operational Competencies in Maritime Logistics Education and Practice - Akhmad Gifari Multazam, Rizal Rochmansyah (Meteor STIP Marunda, 2025)
This research explores how port digitalization reshapes the competency requirements of maritime logistics professionals and evaluates whether current educational programs adequately address these new demands. Focusing on medium-sized container terminals that have adopted terminal operating systems, port community systems, and electronic data interchange, the study first maps digital workflows from vessel arrival to cargo release. Operational data on vessel turnaround time, crane productivity, and documentation lead times are analyzed to illustrate efficiency gains. Parallel to this, curriculum content from selected maritime universities and training centers is reviewed, and surveys are conducted among students, alumni, and port practitioners to identify perceived skill gaps in areas such as data analytics, system integration, and digital collaboration. The findings reveal mismatches between rapidly evolving digital practices in ports and the relatively static nature of some academic curricula. The paper proposes a competency-based framework and sample course modules that embed real port data, digital case studies, and industry-led projects to better align maritime education with the digital transformation of port and shipping management.